Pengaruh LDR dan CAR terhadap Harga Saham Bank Rakyat Indonesia Periode 2017-2023 - Efriyanto, Efriyanto; Azali, Aprilia (Politeknik Negeri Jakarta, 2024)
Information that is relevant and capable of providing signals in considering investment decisions, to predict stock prices is really needed by investor. The purpose of this research is to examine the effect LDR and CAR on the stock price at Bank Rakyat Indonesia period 2017-2023. The secondary data used comes from the Quarterly Financial Statements published on the official BRI website for 2017-2023. Purposive sampling technique is the technique applied in sampling. The analysis method applied is multiple linear regression. Data processing and analysis using the application SPSS version 29. The results of this research partially show that LDR has no effect on the stock prices, meanwhile CAR have a positive and significant effect on the stock prices. Simultaneously, LDR and CAR have a significant effect on the stock prices. Keywords: LDR, CAR, Stock Price